(untitled) (Journal of Parents and Teachers, 2018)
This article intends to show a general vision about the development of education programmes and actions that connect the Museum and the School at Thyssen-Bornemisza National Museum. The ultimate goal is to outline the guidelines for the future. It focuses on the transformation throughout years of programmes and real situations: from school visits to academic training of teaches, from the latest costum-made visits to the experience with future teachers, or the experimental communities with teachers.